Implementasi Kebijakan Identitas Kependudukan Digital (IKD) di Kota Mojokerto - Ramadhan, Rizky Bagus; T, Tauran; Prabawati, Indah; Hilmi, Ahmad Nizar (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Digital Population Identity (Identitas Kependudukan Digital/IKD) is a national policy aimed at supporting the digital transformation of population administration to improve the quality of public services. This study aims to analyze the implementation of the IKD policy in Mojokerto City using the policy implementation framework of Van Meter and Van Horn. This research employs a qualitative descriptive approach, with data collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman model. The results indicate that the implementation of IKD has been carried out but has not yet been optimal. Policy standards and objectives have been clearly established; however, the achievement of IKD activation targets has not met the predetermined goals. Human resources and infrastructure are relatively adequate, but technical problems in the application and low levels of digital literacy among the community remain challenges. Policy socialization has not reached all segments of society evenly. These findings suggest that the success of IKD implementation is influenced not only by clear standards and sufficient resources, but also by implementers’ disposition and the social readiness of the target community.